2019
DOI: 10.1177/2233865919871702
|View full text |Cite
|
Sign up to set email alerts
|

Democracy, consumption, and growth in sub-Saharan Africa

Abstract: This article studies the effect of political regime type on economic growth in sub-Saharan Africa. Democracy promotes growth because it conditions government consumption so that consumption is used for public purposes rather than private needs and this in turn leads to faster growth. By conditioning consumption towards public goods and away from private goods, we should see that consumption in democratic regimes is associated with more public goods like roads and education while in authoritarian regimes consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 80 publications
(80 reference statements)
5
4
0
Order By: Relevance
“…Thus, similar argument can be given for the negative effect of political regime reported in models 1–2 of Table 4. The positive effect of political regime on economic growth in model 4 is in line with arguments by Doces (2020), Asiedu (2016), and Veisi (2017) that strong democratic regime suppports economic growth by enhancing infrastructure; supporting foreign direct investments as well as entrepreneurial development; and the promotion of civil rights, human rights, and rule of law for its citizens, respectively.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Thus, similar argument can be given for the negative effect of political regime reported in models 1–2 of Table 4. The positive effect of political regime on economic growth in model 4 is in line with arguments by Doces (2020), Asiedu (2016), and Veisi (2017) that strong democratic regime suppports economic growth by enhancing infrastructure; supporting foreign direct investments as well as entrepreneurial development; and the promotion of civil rights, human rights, and rule of law for its citizens, respectively.…”
Section: Resultssupporting
confidence: 82%
“…They, however, concluded that evidence for or against the resource curse hypothesis is dependent on the prevalence of specific conditions. Although the effect of political regime on economic growth has been examined empirically for different countries and regions with varied outcomes (Doces, 2020; Okunlola, 2019), there is little evidence on how regime type interacts with natural resources to influence economic growth. It is in this regard that the study analyses the effect of the interaction between natural resource and political regime on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, urbanization seems to work against the major objective it was supposed to promote. This analysis shows that it does so because urbanization increases corruption, which as we know is a major determinant of economic growth and social well-being (Doces, 2020;Gyimah-Brempong, 2002;Mauro, 1995). This finding is consistent with Henderson (2003) who posits that urbanization is not a synonym for development, and also Fox (2013) who shows that economic growth does not follow urbanization in Sub-Saharan Africa as it does in other parts of the world.…”
Section: Discussionsupporting
confidence: 87%
“…Instead, urbanization seems to work against the major objective it was supposed to promote. This analysis shows that it does so because urbanization increases corruption, which as we know is a major determinant of economic growth and social well-being (Mauro, 1995;Gyimah-Brempong, 2002;Doces, 2020). This finding is consistent with who posits that urbanization is not a synonym of development, and also Fox (2013) who shows that economic growth does not follow urbanization in Sub-Saharan Africa as it does in other parts of the world.…”
Section: Discussionsupporting
confidence: 84%